Brothers of the head - Aldiss, Brian Wilson 1925-2017 (Genius Products [u.a.], 2006)
In the 1970s a music promoter plucks Siamese twins from obscurity and grooms them into a freakish rock'n'roll act. A dark tale of sex, strangeness and rock music. [IMDb]
Bildformat 1.85:1
Orig.: Großbritannien 2005
Enth. deleted scenes with uncut, never-before-seen footage